2017
DOI: 10.1093/treephys/tpx124
|View full text |Cite
|
Sign up to set email alerts
|

Why size matters: the interactive influences of tree diameter distribution and sap flow parameters on upscaled transpiration

Abstract: In stands with a broad range of diameters, a small number of very large trees can disproportionately influence stand basal area and transpiration (Et). Sap flow-based Et estimates may be particularly sensitive to large trees due to nonlinear relationships between tree-level water use (Q) and tree diameter at breast height (DBH). Because Q is typically predicted on the basis of DBH and sap flow rates measured in a subset of trees and then summed to obtain Et, we assessed the relative importance of DBH and sap f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 66 publications
2
12
0
Order By: Relevance
“…The linear relationship of SFD, with DBH, wood area and the crown projected area reported in our study (table 1) was also documented by other researchers (Kallarackal et al, 2012;Berry et al, 2017). The relationship between crown projected area and sap ow is explained by the pipe model theory (Shinozaki et al, 1964).…”
Section: Sap Ow Characteristicssupporting
confidence: 90%
“…The linear relationship of SFD, with DBH, wood area and the crown projected area reported in our study (table 1) was also documented by other researchers (Kallarackal et al, 2012;Berry et al, 2017). The relationship between crown projected area and sap ow is explained by the pipe model theory (Shinozaki et al, 1964).…”
Section: Sap Ow Characteristicssupporting
confidence: 90%
“…Basal area can be an indicator of competition intensity early in succession because low initial basal area can reflect more space available for recruitment and growth. Conversely, high initial basal area may accelerate sapling mortality and slow sapling biomass accretion because patches with more basal area transpire more water (Berry et al, ) probably leaving little soil moisture left for saplings. Moreover, our results resemble what van Breugel et al () found in a successional forest in Mexico, where mortality via self‐thinning was higher than recruitment along a gradient from high initial basal area to low initial basal area.…”
Section: Discussionmentioning
confidence: 99%
“…These ecophysiological traits, such as wood anatomy, rooting depth, stomatal density, sapwood density, have evolved through competition and adaptation by co-occurring species belonging to different functional groups, and are expressed as inter-specific variability (between individuals of different species) (Phillips et al 2010, Hernandez-Santana et al 2015. The intra-specific (within individuals of the same species) variations manifests as radial and azimuthal variability in sap flow, and are influenced by growth stages, size, and individual responses to the microclimate (Fiora and Cescatti 2006, Berdanier et al 2016, Berry et al 2018). Such species-based understanding is important while scaling transpiration to individual and stand-levels, which requires using appropriate scalars, including biometric scalars like sapwood area, leaf area index (LAI), basal area, and tree height (Hatton et al 1995, Barbour et al 2005, Mackay et al 2010.…”
Section: Introductionmentioning
confidence: 99%